Examining impairment and distress from food addiction across demographic and weight groups. (December 2021) - Carr, Meagan M.; Lawson, Jessica L.; Wiedemann, Ashley A.; Barnes, Rachel D.
Abstract: Rates of food addiction (FA) vary across weight and demographic groups. Factors influencing discrepant prevalence rates are largely unknown. Rates of clinically significant distress or impairment also vary across demographic groups, yet prior studies have overlooked the diagnostic significance of distress/impairment in heterogenous groups. We tested if weight and demographic groups differed in their likelihood of endorsing distress/impairment from FA. Participants ( N  = 1832) recruited from Amazon Mechanical Turk completed the modified Yale Food Addiction Scale 2.0 (mYFAS). The mYFAS includes 11 dichotomous symptom indicators and one dichotomous distress/impairment indicator. Differences in distress/impairment were tested across weight, sex, racial/ethnic, and educational groups using logistic regression. FA severity was controlled for using FA symptom count. There were no differences among racial/ethnic and educational groups ( p  > 0.05). Compared to men, women were more likely to report distress/impairment (aOR = 1.96, 95% CI = 1.28–3.03). People with obesity were more likely to report distress/impairment compared to people with overweight (aOR = 2.20, 95% CI = 1.39–3.49) or normal weight (aOR = 1.99, 95% CI = 1.26–3.13). Individual characteristics (i.e., sex, weight) may influence reporting of distress/impairment from FA. Further inquiry may be appropriate for men and people with normal weight or overweight presenting with FA symptoms who otherwise deny distress/impairment. Highlights: Distress and impairment are important, understudied features of food addiction (FA) Education and racial/ethnic identity did not appear to influence the experience of FA symptoms as distressing/impairing Women and people with obesity were more likely to experience FA symptoms as distressing/impairing